Poly (lactic acid)/Poly (butylene adipate-co-terephthalate) films with simultaneous high oxygen barrier and fast degradation properties - Mengjing Yang; Yuxi Mao; Penghui Zhang; Jie Li; Zeming Tong; Zhenguo Liu; Yanhui Chen (Green Energy & Environment)
Although poly (lactic acid) (PLA) is a good environmentally-friendly bio-degradable polymer which is used to substitute traditional petrochemical-based polymer packaging films, the barrier properties of PLA films are still insufficient for high-barrier packaging applications. In this study, oxygen scavenger hydroxyl-terminated polybutadiene (HTPB) and cobalt salt catalyst were incorporated into the PLA/poly (butylene adipate-co-terephthalate) (PLA/PBAT), followed by melting extrusion and three-layer co-extrusion blown film process to prepare the composite films. The oxygen permeability coefficient of the composite film combined with 6 wt% oxygen scavenger and 0.4 wt% catalyst was decreased significantly from 377.00 cc·mil·m−2·day−1·0.1 MPa−1 to 0.98 cc·mil·m−2·day−1·0.1 MPa−1, showing a remarkable enhancement of 384.69 times compared with the PLA/PBAT composite film. Meanwhile, the degradation behavior of the composite film was also accelerated, exhibiting a mass loss of nearly 60% of the original mass after seven days of degradation in an alkaline environment, whereas PLA/PBAT composite film only showed a mass loss of 32%. This work has successfully prepared PLA/PBAT composite films with simultaneously improved oxygen barrier property and degradation behavior, which has great potential for high-demanding green chemistry packaging industries, including food, agricultural, and military packaging.